Curcumin and Intestinal Oxidative Stress of Pigs With Intrauterine Growth Retardation: A Review - Tang, Xiaopeng; Xiong, Kangning; Wassie, Teketay; Wu, Xin (Frontiers in Nutrition, 2022)
Intrauterine growth restriction (IUGR) refers to the slow growth and development of a mammalian embryo/fetus or fetal organs during pregnancy, which is common and causes considerable economic losses in swine production. Nutritional strategies have been reported to improve the health status and growth performance of IUGR piglets, among which dietary curcumin supplementation is an efficient way. Curcumin is a natural lipophilic polyphenol derived from the rhizome of Curcuma longa with many biological activities. It has been demonstrated that curcumin promotes intestinal development and alleviates intestinal oxidative damage. However, due to its low bioavailability caused by poor solubility, chemical instability, and rapid degradation, the application in animal production is limited. In this review, we summarized the structural-activity relationship to enhance the bioavailability, and the nutritional effects of curcumin on intestinal health from the aspect of protecting piglets from IUGR associated intestinal oxidative damage. This review provides a theoretical basis to improve the application of curcumin in animal production.